Implementing Instructional Practices to Improve American Indian and Alaska Native Students' Reading Outcomes: An Exploration of Patterns Across Teacher, Classroom, and School Characteristics. (November 2017) - Vincent, Claudia; Tobin, Tary; Van Ryzin, Mark
The Native Community strongly recommends integrating Native language and culture (NLC) into reading instruction to improve outcomes for American Indian/Alaska Native (AI/AN) students. However, little is known about the extent to which recommended practices are used and what might facilitate their implementation. The National Indian Education Study conducted by the U.S. Department of Education surveys teachers of AI/AN students on their instructional practices. This descriptive study builds on previous analysis of survey data, which identified measurable dimensions of NLC in instruction. We now examine (a) the extent to which teachers implement these dimensions and (b) what teacher, classroom, and schoolwide characteristics facilitate implementation. Outcomes suggest that the recommended practices are rarely implemented, and that AI/AN teachers speaking Native language(s) and teaching in classrooms with high AI/AN enrollment located in schools employing AI/AN teachers and staff implement the recommended practices more often. We discuss implications for teacher education and support.